ANALISIS PERAN DIVISI SATUAN KERJA AUDIT INTERNAL DALAM MITIGASI RISIKO PROSES PEMBIAYAAN (STUDI KASUS: PT BANK KB BUKOPIN SYARIAH BUKITTINGGI) - Alena Tiosa; Zuwardi Zuwardi (CV. ADIBA AISHA AMIRA, 2023)
This research is a field research with a qualitative method that connects theory with facts using primary data sources and secondary data. Data collection techniques using document studies, observations, and interviews. Based on the results of the research that the authors have done, it can be interpreted that the role of the internal audit work unit division in managing the risk of the financing process at PT. Bank KB Bukopin Syariah Bukittinggi, aims to prevent financing risks that can harm the bank, such as a decrease in the number of customers, incomplete data from prospective customers, as well as repeated findings in the financing inspection process, therefore auditing the role of the unit internal work in handling the risk of the financing process is very important in supporting the management and risk mitigation of the financing process, then several internal audit roles are carried out in identifying financing risks at PT Bank KB Bukopin Syariah Bukittinggi such as ensuring compliance, credit quality assessment, testing of financing procedures, checking portfolio Financing, overcoming fraud and protection, as well as reporting and recommendations, by carrying out this role, the financing process will run according to the provisions. The stages of carrying out inspections by the internal audit work division in handling the risk of the financing process at PT Bank KB Bukopin Syariah Bukittinggi, include audit planning, information gathering, evaluation and risk assistance, development of audit plans, audit implementation, analysis of findings and completion of reports and follow-up follow up on audit results.